The causes of construction dispute on client organizations - Koh, Cheo Poh (2005)
Construction projects are increasingly complex, resulting in complex contract documents. Complex construction can likewise result in complex disputes. Dispute is inevitable in construction projects which predominantly arise from complexity and magnitude of works, multiple prime contracting parties, poorly prepared and /or executed contract documents, inadequate planning, financial issues and communication problems. Any one of these factors can overturn a project and lead to complicated litigation and arbitration, increased costs, time overrun, and a breakdown in the parties’ interest and relationship. Thus, the objectives of this study are to study and identify the causes of construction dispute as well as its impact on client’s organization. This paper also reviews the causes of dispute contributed by clients, designers and contractors in construction project and suggestion on how to minimize or avoid the occurrences of construction dispute. A questionnaire survey was carried out in the state Johor Bahru and the feedbacks were analyzed using important index (Likert Scale) and average index analysis. The results show that people, process, and project all contribute to such dispute potential. Overall, the respondents are agreed that unresolved construction disputes will only bring negative impact on client’s organization which is time and cost overruns, diminution of respect between parties-deterioration of relationship and breakdown in cooperation and additional expenses in managerial and administration.